Global Trends in Public Service Quality Research: Bibliometric Analysis and Network Visualization Based on VOSviewer - Alya Syafitri Lubis; Naurah Athaya; Adellah Adellah (Eastasouth Institute, 2026)
This study conducts a bibliometric analysis of public service quality literature indexed in the Dimensions database over 2020–2024. A total of 390 documents were analyzed using VOSviewer to map publication trends, influential contributors, collaboration networks, and thematic evolution. Publication productivity peaked in 2023 with 111 documents, driven by growing academic interest following the COVID-19 pandemic. The United States dominated with 222 documents, followed by the Netherlands, the United Kingdom, and China. Co-authorship network analysis identified three major intellectual clusters, with Jeremy L. Hall as the most productive author. Keyword overlay visualization revealed a paradigmatic shift from bureaucratic representation toward evidence-based governance transformation.